On the Reception of the Myth of Prometheus in Austrian Literature of 19th-20th Centuries - A. E. Kachorovskaya (Tsentr nauchnykh i obrazovatelnykh proektov, 2020)
This article focuses its attention on the motive of resistance characteristic of Austrian literature of the 19th - 20th centuries, which is considered from the point of view of the historical and literary relationship with the myth of Prometheus. The history of the issue is reviewed. A selective analysis of the versions of the Promethean myth in the Austrian historical and literary context of the 19th-20th centuries, which is part of the pan-European literary and philosophical heritage, is given. The stylistic and genre originality of Austrian interpretations of the myth of Prometheus is proved on the basis of a study of a number of works. The artistic reception of the image of Prometheus in the poem by Z. Lipiner "Liberated Prometheus", little studied in Russian literary criticism is considered in the article. Attention is paid to the version of the Promethean myth in the literature of Austrian Art Nouveau (on the example of F. Kafka's little prose). The issue of conflicting trends in the development of Austrian literature of the 20th century, affecting the interaction of the motive of resistance with the Promethean myth, is investigated by the example of M. Gruber's essay. The correlation of the Austrian versions of the motive of resistance with the myth of Prometheus is proved. The results of the study confirm the significance of the Promethean myth in the Austrian reception of the 19th-20th centuries, which has more pronounced features of drama and theatricality in relation to the European context.